(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2023)
Objective: The study aims to describe how the self-perception of independence and physical condition of untrained older people were affected in the first year of the pandemic. Methodology: A longitudinal, descriptive study was developed in which the levels of self-perception of independence and physical condition of this age group were assessed. For this, four surveys were carried out during the year 2020 among older people belonging to the clubs of the house of the elderly in the municipality of Talca. The surveys were carried out during the months of January, April, July, and October of the year 2020, a non-probabilistic sample for convenience. Originally, a total of 122 people belonging to 8 clubs for the elderly in the city of Talca agreed to participate, ending the study with 96 people; the rest could not continue follow-up for various reasons. Result: the IFIS scale in 2020 suffered a decrease of 26.86% on average, and the CPF scale suffered an average annual decrease of 17.15%. Another important point to highlight has to do with the fact that there are statistically significant differences (p < 0.05) between the month of January (taken as a reference) and the months of April, July, and October. Conclusion: For both IFIS and CPF surveys, there are statistically significant differences (p < 0.05) between the month of January (taken as a reference) and the months of April, July, and October, which can be translated into the fact that the changes suffered were important and possibly influenced due to the onset of the pandemic. As time passed, these changes were not reversed in the same way that they were imposed.